An empirical assessment of corporate governance components and their impact on profitability: evidence of listed banks in Indonesia - Ahmad Mukoffi; Hendrik Suhendri; Dwi Hastuti; Meliyana Meliyana; Sri Indah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This study aims to determine the effect of business size, capital structure, audit committee, board of directors, and board of commissioners on company profitability in banking companies listed on the Indonesia Stock Exchange from 2018 to 2021. A total of 42 banking companies are the study sample. A purposive sampling technique was used to get 10 sample companies for 4 years with 40 observations. The research data comes from a sample of companies from the Indonesian Stock Exchange website. Multiple regression analysis and descriptive statistical analysis are the data analysis methods used. The research findings show that company size affects profitability, but the board of directors, board of commissioners, audit committee, and capital structure do not affect company profitability.